2015
DOI: 10.1038/srep14244
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Transcriptional Complexity of the Receptive and Pre-receptive Endometria of Dairy Goats

Abstract: Endometrium receptivity is essential for successful embryo implantation in mammals. However, the lack of genetic information remains an obstacle to understanding the mechanisms underlying the development of a receptive endometrium from the pre-receptive phase in dairy goats. In this study, more than 4 billion high-quality reads were generated and de novo assembled into 102,441 unigenes; these unigenes were annotated using published databases. A total of 3,255 unigenes that were differentially expressed (DEGs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 138 publications
5
31
2
Order By: Relevance
“…What's more, the expression level of NTS increased 195-fold in the endometrium in RE compared to PE (Figure 3B), which was in accordance with the previous sequencing date [20]. Immunohistochemistry (IHC) results further showed NTS protein increased in RE (Table 2), especially in the EECs (Figure 3C-3F).…”
Section: Mir-181a and Nts Were Differentially Expressed In The Pe And Resupporting
confidence: 76%
See 1 more Smart Citation
“…What's more, the expression level of NTS increased 195-fold in the endometrium in RE compared to PE (Figure 3B), which was in accordance with the previous sequencing date [20]. Immunohistochemistry (IHC) results further showed NTS protein increased in RE (Table 2), especially in the EECs (Figure 3C-3F).…”
Section: Mir-181a and Nts Were Differentially Expressed In The Pe And Resupporting
confidence: 76%
“…NTS mRNA levels decreased 6.08-fold in RE compared with PE in dairy goats, but this result was inconsistent with the previous what reported that NTS remarkably increased in RE [20]. What's more, a total of 668 DElncRs were found and the full list was provided in Supplementary File 3, and TCONS_00376915 (lncR915) was significantly higher in RE compared with PE.…”
Section: Resultscontrasting
confidence: 52%
“…On the day of sponge removal (day 11), each goat received an intramuscular injection of 0.1 mg prostaglandin F2α and 200 IU pregnant mare's serum gonadotropin (PMSG) (Ningbo Pharmaceutical Co., Ltd.). The experimental goats were observed three times daily to ascertain the estrous sign, and mated naturally twice in estrus (Lei et al, ; Liu et al, ; Zhang et al, ). The 12 experimental goats were observed three times daily to ascertained estrous sign, and the first day of estrus was considered to be day 0 (ED0).…”
Section: Methodsmentioning
confidence: 99%
“…Transcriptomics is a powerful tool to identify potential molecular biomarkers for endometrial receptivity, thereby improving forecasts of pregnancy outcome during in vitro fertilization treatment (Wang & Yu, ). Transcriptome analyses of distinct physiological stages were crucial for understanding the gene regulatory network, including the endometrium development in mammals (Wang et al, ; Zhang et al, , ). Moreover, studies on the endometrial transcriptomics have been reported using RNA‐Seq in humans (Hu et al, ), pigs (Lin et al, ; Samborski, Graf, Krebs, Kessler, & Bauersachs, ; Samborski, Graf, Krebs, Kessler, Reichenbach, et al, ; Wang et al, ), cattles (Mamo, Mehta, Forde, Mcgettigan, & Lonergan, ; Palma‐Vera, Sharbati, & Einspanier, ), and goats (Zhang et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…The first day of mating was considered to be day 0 of pregnancy. Endometrium samples from five goats at gestational day 5 and five goats at gestational day 15 were obtained from the anterior wall of the uterine cavity (Song et al., ; Zhang, An et al., ). The tissue samples were washed briefly with PBS (Phosphate Buffered Saline) and then immediately frozen in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%